Momentum Factor Effects in Emerging Markets An Analysis of ASEAN Countries - romayanis lbgaol; Evi Nur Cahyanti (Cv. Data Sinergi Digital, 2025)
This study examines the role of momentum factors in portfolio formation across relatively illiquid ASEAN stock markets. Grounded in the Efficient Market Hypothesis (EMH), the study investigates whether past stock returns provide predictive information for future returns in emerging markets characterized by heterogeneous liquidity, volatility, and investor behavior. Using a quantitative approach, the study analyzes secondary data from large firms consistently listed in Indonesia, Malaysia, the Philippines, and Thailand during the 2020–2024 period. Stock price and firm-level data were obtained from Bloomberg, Refinitiv, and Yahoo Finance, while non-price variables included ESG scores, corporate governance ratings, market capitalization, and selected macroeconomic indicators. The analysis employed winner-minus-loser (WML) portfolio construction, Pearson correlation, Ordinary Least Squares (OLS) regression, and classical assumption tests. The findings reveal that lagged returns have a negative and statistically significant effect on current returns at the annual horizon, indicating the presence of mean reversion rather than persistent annual momentum. However, medium-term momentum effects remain evident in more liquid markets, particularly Indonesia and Malaysia. In contrast, the Philippines is dominated by reversal patterns, while Thailand shows a stronger relationship between ESG scores and stock returns. These results suggest that momentum effects in ASEAN markets are heterogeneous and highly dependent on liquidity, market depth, investment horizon, and sustainability-related factors. The study contributes to the literature on market anomalies by showing that momentum strategies in emerging markets require context-specific portfolio designs.